Improving environmental activities of oil companies using advanced management technology - Гавадзин, Н. О. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2014)
The quality of the environment causes considerable interest during the last decades which indicates the change in society’s attitude towards events, which occur in it. That’s why there is a growing interest in the management of companies’ environmental protection activities. Nowadays the ecological problems grow worse and they demand immediate solution. The companies’ environmental protection activity in Ukraine is not effective because it doesn’t take into consideration latest improvement tendencies, the peculiarities of oil and gas industry and modern management techniques of its efficiency improvement. The oil and gas companies’ environmental protection activity should be directed to the advancement and maintenance rather than restoration and improvement. That’s why the management of environmental protection activity, for its improvement, should be done using the progressive management technologies. Monitoring, foresight, outsourcing, reengineering, benchmarking, structural changes, kaizen-technology, design for Six Sigma, balanced indexes system and controlling can become such progressive technologies of the oil and gas companies’ environmental protection activity. Not taking into account ecological factors while managing the company or marking them as side effects of economic growth endangers can lead to considerable material and financial losses, which can cause the negative economic effect. The suggested technologies of environmental protection activity management can help to prevent, effectively regulate or solve ecologic-economical problems, in particular, and would promote efficiency improvement of the functioning of the companies of oil and gas complex in general.